G244(P) Effects of Maternal Preeclampsia on Neonatal Immune Cell Frequencies, Cytokine and Cortisol Levels During the First Week of Life. (24th May 2017) - Toldi, G; Sava, F; Treszl, A; Hajdu, J; Harmath, A; Rigo, J; Tulassay, T; Vasarhelyi, B
Abstract : Preeclampsia (PE) is characterised by a systemic maternal inflammatory response and reduced immune tolerance towards the developing fetus. Yet, little is known about the impact of maternal PE on the fetal immune system. We investigated the frequency of distinct immune cell subsets and plasma cortisol and cytokine levels in preterm infants of PE mothers during the first week of life and compared them to preterm infants born from pregnancies not complicated by PE. Cord blood and peripheral blood samples on the 1st, 3rd, and 7th days of life were collected from 14 preterm infants affected by PE (median GA: 30 weeks, BW: 985 g) and 14 controls (median GA: 29 weeks, BW: 1180 g). Ethical approval was obtained from the institution (Semmelweis University). We measured plasma cortisol and cytokine levels and also assessed the prevalence of T, NK and dendritic cell (DC) subsets and activation markers using flow cytometry, using the following antibodies: CD3, CD4, CD8, CD25, CD45RA, CD45RO, CD62L, CD69, CD161, CXCR3, CCR4, HLA-DR, 6 B11, CD11c, CD123. The prevalence of CD4+ T lymphocytes and CD4+HLA-DR + T cells was significantly lower in preterm infants of PE mothers on day 3 compared with controls. The prevalence of memory T cells (CD4+ CD45RO+) was significantly higher in PE infants on day 7. CD8+CD69+ activated T lymphocytes had a lower prevalence on days 0 and 1 in preterm infants born to PE mothers. Myeloid DCs (CD11c+) had a lower prevalence on days 1 and 3 in PE infants. The prevalence of NK cell subsets was comparable in both groups. MCP-1 and IL-4 had significantly higher levels on all 3 postnatal days in infants of PE mothers, while cytokine levels were generally lower at birth compared with controls. Cortisol levels were lower in PE infants on day 1 and 7, respectively. Our observations show that PE has a remarkable impact on the development of the newborn's immune status during the first week of life by influencing the prevalence of distinct immune cell subsets as well as plasma cytokine and cortisol levels.